Study the pharmacological potential of 1,2,4-thiadiazine 1,1-dioxides: A minireview - Hiba Ali Hasan; Mesoun A. A. Al-N (College of Pharmacy / Mustansiriyah University, 2023)
Study of the pharmacological activity of new heterocyclic scaffolds becomes a passion of many medicinal chemists around the world.  1,2,4-thiadiazine 1,1-dioxide derivatives are one of the heterocyclic derivatives that haveattracted researchers' attention since the early 1940's. In spite of this, however, the study of the pharmacological activities of this nucleus remains scant and needs to shed lighter on it. Therefore, in this review, the authors in this review collected all the families that included this nucleus whose biological activities were studied for the period between 1993 and 2020 in order to get an idea of the effectiveness of these compounds and highlighted the most effective ones. In addition, knowing the pharmacological aspects that had not been studied previously to focus more on them in the future by interested researchers.